AMPKα promotes basal autophagy induction in Dictyostelium discoideum. Issue 5 (3rd November 2019) - Maurya, Ranjana; Kumar, Rakesh; Saran, Shweta
Abstract: Autophagy is a degradation process, wherein long‐lived proteins, damaged organelles, and protein aggregates are degraded to maintain cellular homeostasis. Upon starvation, 5′‐AMP‐activated protein kinase (AMPK) initiates autophagy. We show that ampkα − cells exhibit 50% reduction in pinocytosis and display defective phagocytosis. Re‐expression of AMPKα in ampkα − cells co‐localizes with red fluorescence protein‐tagged bacteria. The ampkα − cells show reduced cell survival and autophagic flux under basal and starvation conditions. Co‐immunoprecipitation studies show conservation of the AMPK–ATG1 axis in basal autophagy. Computational analyses suggest that the N‐terminal region of Dd ATG1 is amenable for interaction with AMPK. Furthermore, β‐actin was found to be a novel interacting partner of AMPK, attributed to the alteration in macropinocytosis and phagocytosis in the absence of AMPK. Additionally, ampkα − cells exhibit enhanced poly‐ubiquitinated protein levels and allied large ubiquitin‐positive protein aggregates. Our findings suggest that AMPK provides links among pinocytosis, phagocytosis, autophagy, and is a requisite for basal autophagy in Dictyostelium . Abstract : Co‐immunoprecipitation studies show the conservation of the AMPK–ATG1 axis in basal autophagy. β‐actin was found as a novel interacting partner of AMPK, attributed to the alteration in macropinocytosis and phagocytosis in the absence of AMPK. Our findings suggest that AMPK provides links among pinocytosis, phagocytosis, and autophagy, and is requisite for basal autophagy in Dictyostelium.